2013
DOI: 10.1038/tp.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor hyperactivity in 14-3-3ζ KO mice is associated with dopamine transporter dysfunction

Abstract: Dopamine (DA) neurotransmission requires a complex series of enzymatic reactions that are tightly linked to catecholamine exocytosis and receptor interactions on pre- and postsynaptic neurons. Regulation of dopaminergic signalling is primarily achieved through reuptake of extracellular DA by the DA transporter (DAT) on presynaptic neurons. Aberrant regulation of DA signalling, and in particular hyperactivation, has been proposed as a key insult in the presentation of schizophrenia and related neuropsychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
2
27
2
Order By: Relevance
“…We found that 14-3-3ζ KO mice display several schizophrenia-like behavioural deficits such as hyperactivity and disrupted sensorimotor gating, impaired novel object recognition, impaired learning in a water crossmaze escape task, and lower levels of anxiety in the elevated plus maze (Cheah et al, 2012). As previously reported, we found that clozapine ameliorated hyperactivity in 14-3-3ζ KO mice (Ramshaw et al, 2013). Anatomically, we have identified neuronal migration defects, disrupted mossy fibre circuits, and aberrant synaptic terminals in the hippocampi of 14-3-3ζ KO mice (Cheah et al, 2012).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that 14-3-3ζ KO mice display several schizophrenia-like behavioural deficits such as hyperactivity and disrupted sensorimotor gating, impaired novel object recognition, impaired learning in a water crossmaze escape task, and lower levels of anxiety in the elevated plus maze (Cheah et al, 2012). As previously reported, we found that clozapine ameliorated hyperactivity in 14-3-3ζ KO mice (Ramshaw et al, 2013). Anatomically, we have identified neuronal migration defects, disrupted mossy fibre circuits, and aberrant synaptic terminals in the hippocampi of 14-3-3ζ KO mice (Cheah et al, 2012).…”
Section: Introductionsupporting
confidence: 88%
“…Previous studies in 14-3-3ζ -depleted mice have reported a beneficial effect of clozapine on isolated behavioural paradigms such as hyperactivity (Ramshaw et al, 2013;Foote et al, 2015) and prepulse inhibition (Foote et al, 2015). The incorporation of a more comprehensive test battery in our study shows that clozapine effects are not clear-cut in this model.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Compared with WT, the 14-3-3 FKO mice had a higher DA level in the striatum (Figure 2A), but not in the cortex (Figure 2B). While 14-3-3 proteins have been implicated in regulating DA synthesis and transport (46), transgene expression in the 14-3-3 FKO mice was not detected within the dopaminergic neurons of the Ventral Tegmental Area (VTA) and the Substantia Nigra pars compacta (SNc) (Figure 2C), or their processes in the striatum (Figure 2D). Thus, the elevated striatal DA level of the 14-3-3 FKO mice is unlikely a direct consequence of 14-3-3 inhibition in DA producing neurons and their terminals.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, similar findings were reported for the 14-3-3ζ knockout mice, including increased striatal DA content and antipsychotic drug effectiveness on locomotor hyperactivity (55). Additionally, the 14-3-3ζ mice were shown to have a reduced level of the DA transporter (DAT), suggesting a direct role for 14-3-3ζ in regulating DA neurotransmission (46). However, in the 14-3-3 FKO mice, transgene expression was not detected in the dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%